DECISIONAL PROCRASTINATION: PREVALENCE AMONG STUDENTS AND RELATIONSHIP WITH EMOTIONAL INTELLIGENCE AND BIG FIVE-FACTOR MODEL OF PERSONALITY: Life Sciences-Psychology - FARSHAD SHEYBANI; BANAFSHEH GHARRAEE; MAHDI BAKHSHIZADEH; SHIMA TAMANAEEFAR (International Journal of Life Science and Pharma Research, 2022)
Studies indicate that approximately 80-95% of university students are involved in procrastination. The previous studies show that decisional procrastination may lead to poor academic performance, experience of unwilling emotions like self-feeling of being shameful and guilty, depression, negative health behaviors such as delay in addressing health problems, and one way for Plagiarism. The present study was aimed at investigation of the decisional procrastination prevalence among the students of universities of Tehran, and its relationship with emotional intelligence and big five-factor model of personality. The students of public and Islamic Azad universities in Tehran made up the statistical population of this research. This study used multistage cluster sampling method as a subsidiary to simple random sampling and 400 students were selected. Participant in the study completed the Decision Problem (DP) scale, Bar-On emotional intelligence test and NEO Five Factor Inventory. To analyze the data, SPSS (13th version) software was used. The highest percentage of decisional procrastination is observed in the moderate category (45%) and then in the mild category (31%). 22.3% of students showed sever decisional procrastination and 1.7% of students showed very sever decisional procrastination. A negative and significant relationship was seen between the total score of emotional intelligence and decisional procrastination (P < 0.001). A negative and significant relationship was seen between the total score of emotional intelligence and neuroticism. There was a positive and significant relationship between the total score of emotional intelligence and Extraversion, agreeableness and conscientiousness in people with severe and very severe decisional procrastination. It appears necessary for planning more serious health programs because procrastination leading to physical and psychological consequences for students.